2003
DOI: 10.1364/ol.28.000831
|View full text |Cite
|
Sign up to set email alerts
|

Electromagnetically induced transparency due to intervalence band coherence in a GaAs quantum well

Abstract: We demonstrate electromagnetically induced transparency in the transient optical response in a GaAs quantum well by using the nonradiative coherence between the heavy-hole and the light-hole valence bands.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
75
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 166 publications
(75 citation statements)
references
References 9 publications
(6 reference statements)
0
75
0
Order By: Relevance
“…24 Experimental results have demonstrated nonradiative relaxation times that are orders of magnitude longer than in QW structures. [25][26][27] There have been studies of midinfrared photodetectors using QDs, 28,29 and optimization issues have been addressed. 30 In addition the room temperature ultraweak absorption of a single buried semiconductor QD was measured.…”
Section: -20mentioning
confidence: 99%
“…24 Experimental results have demonstrated nonradiative relaxation times that are orders of magnitude longer than in QW structures. [25][26][27] There have been studies of midinfrared photodetectors using QDs, 28,29 and optimization issues have been addressed. 30 In addition the room temperature ultraweak absorption of a single buried semiconductor QD was measured.…”
Section: -20mentioning
confidence: 99%
“…where r 3 and r 4 are the decoherence rate for both dipole transitions, and r 2 is the nonradiative decoherence rate [1][2][3][4][5].…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Due to the small effective electron mass, it has advantages of high nonlinear optical coefficients and large electric dipole moments. Several typical interesting phenomena such as electromagnetically induced transparency (EIT) [1][2][3][4][5], lasing without inversion [6], highly efficient four-wave mixing [7], all-optical switching [8], and slow light [1] have been demonstrated. As a method to study quantum coherent control and interference, the relative phase of the applied laser fields has been widely used, which is usually termed as phase control, in several important processes in atomic, molecular, and solid-state systems [9][10][11][12][13][14], but the study of amplification and absorption properties in double-Λ system of GaAs/AlGaAs MQWs has not been reported.…”
mentioning
confidence: 99%
“…[12][13][14][15][16][17][18] For example, Sadeghi et al, 13 in an asymmetric QW, showed that EIT may be obtained with appropriate driving fields, provided that the coherence between the intersubbands considered is preserved for a sufficiently long time. So, quantum coherence and interference in QW structures have attracted great interest due to the potentially important applications in optoelectronics and solid-state quantum information science.…”
Section: -9mentioning
confidence: 99%